The Afterlife of Ophelia - Williams, Deanne. author. aut Link
IX, 262 p. 14 illus.
Keywords: This collection of new essays is the first to explore the rich afterlife of one of Shakespeare's most recognizable characters. With contributions from an international group of established and emerging scholars, The Afterlife of Ophelia moves beyond the confines of existing scholarship and forges new lines of inquiry beyond Shakespeare studies.